Vertical Distributions of Chlorophyl-a in Pinang Luar Oxbow Lake Buluh China Village Siak Hulu Sub District Kampar District Riau Province - Lumbangaol, Perawati Sartika; Siagian, Madju; Sihotang, Clemens (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted of Mei-June 2013 in Pinang Luar Oxbow that is located in the Buluh China Village. This research aims to understand the vertical distributions of chlorophyl-a.Chlorophyl-a samples were collected from 3 stations. In each stations, there are 3 sampling sites, in the surface 1,5 and 2,5 Secchi depth. Sampling was done three times, once a week. Result shown that the chlorophyl-a content ranged from 10,58 – 23,21 μg/l. Water quality parameters values were: depth : 261,7–461,7 cm; temperature: 31 oC; transparency: 65–70 cm; pH: 6; DO: 3,07 – 6,4 mg/l; CO2: 3,96–11,88 mg/l; phosphate: 0,013– 0,019 mg/l and nitrate: 0,030–0,068 mg/l. Chlorophyl-a was higher in the surface than of secchi area. The result showed that Pinang Luar Lake water is mesotrofic and be support the aquatic organism.Key words : Chlorophyl-a, the vertical profiles, Pinang Luar Oxbow